Report of a Working Group on Grain Legumes: Fifth meeting, 7-8 May 2013, Novi Sad, Serbia - Maggioni, L.; Ambrose, M.; Lipman, E.; Bioversity International (2013)
The fifth meeting of the ECPGR Grain Legumes Working Group was held 7-8 May 2013 at Novi Sad, Serbia. The meeting, organized in collaboration with the Institute of Field and Vegetable Crops, Novi Sad, Serbia, brought together 25 participants from 23 countries. Regarding AEGIS, the meeting agreed on a procedure for the selection of candidate accessions for inclusion into the European Collection, to be carried out by the managers of the Lens, Lupinus, Phaselous, Pisum and Vigna Databases. The recently endorsed FAO Genebank Standards were accepted by the Group as suitable for the AEGIS Quality System to be applied to grain legumes; in addition, more detailed regeneration standards will be developed. The current status of the Grain Legumes Central Crop Databases was presented and their relationships with AEGIS and EURISCO discussed. Reports were also given on the national grain legume collections. A major focus of the meeting was the issue of sustaining the Working Group's momentum in the absence of future group meetings. In this view, it was agreed to establish crop-specific interest groups (for Arachis, Cicer, Glycine, Lathyrus, Lens, Lupinus, Pisum, Phaseolus and Vicia faba) and thematic interest groups (Use of grain legumes in sustainable agricultural systems, Exchange of germplasm for evaluation in different environments and AEGIS Quality System development).